Children’s oral folklore ability development (on the basis of folk riddles) - Gučienė, G. (Psichologija, 1968)
Children begin to create them themselves during riddles sessions at kindergarten and the younger classes in primary schools. The author performed a pedagogical experiment to determine 1) when and how children begin to develop riddles, 2) what features distinguish children’s verbal creation of riddles in general and how it differs from folk art, and 3) what educational value it brings to children’s creativity. Educators used a lot of folk riddles and encouraged children’s self-creation in the groups where the experiment took place. Meanwhile, the control class children did not express themselves during independent oral creative work. But after finishing the winter reading topic children in the control class were also asked if they wouldn’t like to think up a winter riddle. The riddles of both classes were analyzed and compared to folklore. Children start coming up with their own riddles when they understand the point of them. (That happens wherever the genre is widely used). We can distinguish three intermediate forms of children’s creative riddles: 1. the riddle formula includes an answer, 2. the riddle formula names the answer’s characteristics and properties (describes them), and 3. Children simplify known folk riddles (e.g., a metaphor replaces direct instruction). Riddles created for preparatory groups of children in most cases already comply with folk riddle structure and traditions. Comparisons occur therein, especially negative ones. Children’s negative comparisons help them understand a metaphor. Metaphors already occur in children’s creative work preparatory groups. Students’ creative work in 2nd grade basically does not do anything new, but merely improves one and the same form. Here is the great value for better absorption of folk traditions (Tables 2 and 3). Children’s riddles in experimental classes stand out more in terms of creative diversity. They depict object properties and action of great diversity. Children’s creative work resulted in a lot of metaphors and comparisons, even more than in actual folk riddles. Aesthetic categories already crop up, such as humor. We examined the development of the experimental class children’s creative riddle about icicles created in the winter. At the end of winter children of all ages were interested in creating riddles and reached a high artistic expressiveness. The children’s verbal creative research accomplished allows us to make some pedagogical conclusions: 1. Making up riddles must be encouraged in both kindergartens and 1st and 2nd grades, as this genre is different from others in its brevity and therefore does not require much time. 2. Making up riddles stimulates children’s observation, imagination, and thinking. 3. Making up riddles activates not only the author, but also entire groups of children, fostering their critical thinking. 4. Making up riddles requires fairly sophisticated and perfect verbal forms of expression that children absorb better than other oral narrative forms. 5. Riddles should be given more time in kindergartens. The current practice of guessing games based on characteristics must at least in part be changed to riddles. 6. It would be appropriate to develop children’s riddle creation at kindergarten and elementary school, without even a special time, simply by rationally integrating it into other classes.